Clinical, histopathological, and immunological responses of ponies to Ehrlichia sennetsu and subsequent Ehrlichia risticii challenge. - Rikihisa, Y (1988)
Ehrlichia risticii has a close antigenic relationship to E. sennetsu. Sera of ponies experimentally infected with E. risticii, the etiologic agent of Potomac horse fever, consistently reacted with E. sennetsu, a human pathogen, in indirect fluorescent-antibody (IFA) testing, while human E. sennetsu convalescent serum reacted with E. risticii by IFA testing and immunoferritin labeling of cells infected in vitro. Two ponies injected intravenously with live E. sennetsu did no develop clinical illness. Subsequent injection with live E. sennetsu did not develop clinical illness. Subsequent injection with live E. risticii also did not induce any disease, in contrast to two control ponies given E. risticii without prior exposure to E. sennetsu. Both controls developed fever, anorexia, depression, dehydration, and diarrhea, which are typical clinical signs of Potomac horse fever, and had characteristic lesions of enteritis and lymph node histiocytosis at postmortem examination. E. sennetsu-exposed ponies had normal gastrointestinal morphologies and lymph node hyperplasia. Ponies primed with E. sennetsu before E. risticii challenge developed high titers of immunoglobulin G antibody which reacted against both E. sennetsu and E. risticii antigens by IFA testing. The most prominent antigenic polypeptide in Western (immuno-) blot analysis of sera collected from ponies primed with E. sennetsu before subsequent challenge with E. risticii was present in lysates of both Ehrlichia species and had an apparent molecular mass of 44 kilodaltons. This band was not prominent in Western blots performed with sera of ponies injected with E. risticii alone. Thus, injection of E. sennetsu protects ponies from clinical and pathological manifestations of the disease induced by injection with E. risticii. Immunologic cross-reactivity of the two organisms with IFA testing and strong immunologic recognition by ponies of the 44-kilodalton antigen common to the two organisms may be related to the development of protective immunity against E. risticii.